Customer Relationship dan Kepuasan Pelanggan Dalam Membangun Loyalitas Pelanggan Produk Agent Eagle Tree Property - Risa Novia Pratama Sari; Tio Minar Evan Seleta (JOURNAL SAINS STUDENT RESEARCH, 2023)
PT. Denadi Mitra Propertindo, or better known as Eagle Tree Property, was established in 2012 in Jakarta. As a company in the property industry, Eagle Tree offers integrated solutions that facilitate clients in acquiring, selling, or managing their assets, including land plots, houses, apartments, shop-houses, and other types of properties. The results of statistical analysis show that overall, the variables of CRM, namely process, technology, and human resources, have a significant influence on customer satisfaction. However, when examining the impact of CRM on customer loyalty, only the technology variable has a significant influence, while the process and human resources variables are not significant. Customer satisfaction is also found to have a significant relationship with customer loyalty. Managerial implications and improvement suggestions for PT Eagle Tree Property have also been explained in the concluding part of this study